Calculating CD Spectra of Flexible Peptides: An Assessment of TD-DFT Functionals - Brkljaca, Zlatko; Malis, Momir; Smith, David M.; Smith, Ana-Suncana (Journal of Chemical Theory and Computation, 2014)
Calculations of CD spectra can provide important structural information for peptide systems. Although TD-DFT is an attractive method for these calculations, recent studies have pointed to problems with modeling charge transfer excitations. Motivated by these problems, we benchmarked the performances of CAM-B3LYP, wB97X-D, M06-2X, B3LYP, and PBE0 against high level ab initio RICC2 calculations for selected peptide structures. Furthermore, we compared the performance of the functionals with the experimentally available data. Our results show that long-range corrected functionals (CAM-B3LYP and wB97X-D) correlate relatively well with RICC2 calculations, as does the meta-hybrid M06-2X, while the global hybrid functionals (B3LYP and PBE0) exhibit the aforementioned charge-transfer artifacts. On the other hand, PBE0 and even more so M06-2X and B3LYP produce spectra in better agreement with the experimental data. We have clarified this apparent discrepancy by finding that the surplus charge-transfer excitations, exhibited by B3LYP and PBE0, seem to have a negligible contribution to the final spectra, once appropriate structural averaging is performed.
Keywords: CIRCULAR-DICHROISM SPECTRA; TRANSITION-METAL-COMPLEXES; HYBRID DENSITY FUNCTIONALS; MOLLER-PLESSET THEORY; IDENTITY APPROXIMATION; MOLECULAR-DYNAMICS; ABSORPTION-SPECTRA; AQUEOUS-SOLUTION; EXCITED-STATES; MODEL CC2